Comparison of viral distribution in duck hepatitis A virus-infected duckling models established by two different methods. (December 2021) - Ming, Ke; Su, Linglin; Zhang, Baokang; He, Miao; Qiu, Tianxin; Wang, Jinli; Meng, Jinwu; Liu, Jiaguo; Wang, Deyun; Wu, Yi
Abstract: Duck hepatitis A virus type 1 (DHAV-1) infection is the main cause of duck viral hepatitis, but the replication process and distribution of DHAV-1 in vivo are still poorly understood. In this study, six-day-old ducklings were infected by two different methods: by intramuscular injection to establish DHAV-1 infection animal models and by the combined administration of virus solution orally, through nasal inhalation, through inoculation of the eye, and through intrarectal contact to simulate natural infection. Tissues were collected at different time points and quantitative real-time polymerase chain reaction (qPCR) was employed to analyze the gene expression levels of DHAV-1 in different tissues. The results showed that the viral gene levels responded to the different challenge methods. Viral gene expression levels in all tissues in the intramuscular injection group were lower than those in the group that simulated natural infection. In both groups, the liver was the primary tissue that responsible for the replication of DHAV-1 genes, as virus gene level peaked at 4 h post infection (hpi). In addition, the respiratory and digestive tracts were important regions for DHAV-1 infection as high viral gene levels were detected at early (8 hpi) and late (96 hpi) stages of infection. This research utilized a novel infection method to simulate natural infection and analyzed the DHAV-1 distribution in different tissues. The findings can provide guidance for making prevention and control measures. Highlights: A novel method was used to establish DHAV-1 infected animal models to simulate natural infection. The DHAV-1 distribution in ducklings in different tissues was firstly studied. This work provided guidance for sound prevention and control of DHAV.